2019
DOI: 10.1007/s12040-018-1052-y
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and geochemistry of a boninite dyke from the western Bastar craton of central India

Abstract: The Dongargarh Supergroup along with the basal Amgaon Gneissic Complex constitutes the northwestern part of the central Indian Bastar craton. In the present study, we report a new finding of a boninite dyke intruded in the Amgaon gneisses of this area. The dyke composed of mainly pyroxenes, amphiboles and subordinate amount of plagioclase. The higher contents of SiO 2 (51-54 wt.%), MgO (12-14 wt.%), Ni (375-473 ppm), Cr (1416-1580 ppm) and very low TiO 2 (0.2-0.4 wt.%) are consistent with the boninite nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…The dykes from Amgaon region represent a subduction related outgrowth of Columbia supercontinent due to the accretion of continental margins [55,56]. Hazarika, et al, (2019) identified mafic dykes of Boninitic compositions from Bastar Craton, earlier described by [63]. This boninite magmatism indicates the presence of remnant subduction-related signatures in the lithospheric mantle formed during the evolution of the Bastar Craton [56].…”
Section: Regional Geologymentioning
confidence: 84%
See 3 more Smart Citations
“…The dykes from Amgaon region represent a subduction related outgrowth of Columbia supercontinent due to the accretion of continental margins [55,56]. Hazarika, et al, (2019) identified mafic dykes of Boninitic compositions from Bastar Craton, earlier described by [63]. This boninite magmatism indicates the presence of remnant subduction-related signatures in the lithospheric mantle formed during the evolution of the Bastar Craton [56].…”
Section: Regional Geologymentioning
confidence: 84%
“…Like figure 6a the high silica samples plot separately with a compositional gap with higher Zr/Ti ratios (Figure 6b). For comparison we have considered published data on Proterozoic mafic magmatic rocks (dykes and flows) from the adjoining areas (Sakoli volcanics: [72], Amgaon Gneissic Complex basaltic and boninitic dykes [55,56], Amgaon Gneissic Complex amphibolitic and doleritic dykes [38] and Khairagarh volcanics [28]. Texturally and mineralogically they are similar to the mafic magmatic rocks of the adjoining areas, as described by the earlier workers [22,26,28,38,55,56,[72][73][74].…”
Section: Magma Typesmentioning
confidence: 89%
See 2 more Smart Citations
“…An intra-cratonic rift model given for the evolution of Dongargarh Supergroup by Neogi et al [19] and references therein, a subduction-related arc-magmatism model for KDMB has been proposed by Asthana et al [3], Khanna et al [10], and Santosh et al [25]. The geochemical signature of boninite dykes from the Dongargarh Supergroup also gives the subductionrelated characteristics [8]. Large igneous provinces model for the emplacement of Paleoproterozoic lamproites dykes [24] and mafic dyke swarms and mantle-derived mafic magmatism [31] in rift environment which was possibly induced by the plume.…”
Section: Introductionmentioning
confidence: 99%